Chemical Laboratory House Keeping: Safety and Practices - Dhital, Khuma Sharma (NUTA Journal, 2019)
A clean lab is safe lab. Good laboratory practice and laboratory housekeeping makes the laboratory quality assurance and quality control. It helps for laboratory safety and management for the reliable and accurate results. Laboratory housekeeping is the fundamental to ensure safe and healthy workplace to work for the staff, teachers and researchers.